Understanding sense of safety and trustworthiness of tourism information among migrant visitors - Preko, Alexander; Gyepi-Garbrah, Theophilus Francis (International Hospitality Review, 2023)
PurposeThe migration-tourism discourse has gained attention in global tourism and mobility among scholars because of the vast contributions of migrant visitors to various sectors of the host country's economy, including the tourism and hospitality industry. However, few studies appear to have been undertaken on the subject matter, particularly within the developing country tourism context. The purpose of this research was to assess and understand migrant visitors' sense of safety among five different nationalities (United Kingdom, USA, Germany, China and India) and their perceptions on trustworthiness of tourism information.Design/methodology/approachAnchored on the national cultural dimension of Hofstede model, this study sampled 306 migrant visitors, with the use of one-way analysis of variance (ANOVA) and the Games–Howell post-hoc test to examine mean differences of nationalities, with regard to trust of tourism information and sense of safety. Finally, the multiple regression analysis was conducted to establish the significant effects of national culture characteristics and trustworthiness of tourism information on sense of safety of migrant visitors.FindingsThe study finds that there were no significant differences in the sense of safety by the five nationalities. However, national culture characteristics (power distance and uncertainty avoidance) and trustworthiness of tourism information were significant predictors of sense of safety of migrant visitors.Research limitations/implicationsThis research adopted only two cultural dimensions of the Hofstede's model, so future studies within the migration-tourism literature should consider adopting other cultural dimensions of the model.Practical implicationsThe research provides, first, insight into sense of safety, trustworthiness of tourism information and national culture characteristics which are relevant for destination marketers, the ministry of tourism and local tourism officials to promote safety tourism.Originality/valueThe study expands the application of the cultural dimension of Hofstede model within the migration-tourism literature and establishes that national cultural characteristics and trustworthiness of tourism information are significant predictors of sense of safety of migrant visitors.